2011
DOI: 10.4149/gpb_2011_01_84
|View full text |Cite
|
Sign up to set email alerts
|

900 MHz pulse-modulated radiofrequency radiation induces oxidative stress on heart, lung, testis and liver tissue

Abstract: Abstract. Oxidative stress may affect many cellular and physiological processes including gene expression, cell growth, and cell death. In the recent study, we aimed to investigate whether 900 MHz pulse-modulated radiofrequency (RF) fields induce oxidative damage on lung, heart and liver tissues. We assessed oxidative damage by investigating lipid peroxidation (malondialdehyde, MDA), nitric oxide (NO x ) and glutathione (GSH) levels which are the indicators of tissue toxicity. A total of 30 male Wistar albino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 28 publications
4
41
1
4
Order By: Relevance
“…Malondialdehyde level was found to be increased in various organs of animals exposed to MWs (19)(20)(21)24,25) including liver (22,26,27). Our results show as well, that MDA levelsare increased in liver tissue of rats exposed to microwaves after prolonged exposition period (40 and 60 days).…”
Section: Disscusionsupporting
confidence: 70%
See 1 more Smart Citation
“…Malondialdehyde level was found to be increased in various organs of animals exposed to MWs (19)(20)(21)24,25) including liver (22,26,27). Our results show as well, that MDA levelsare increased in liver tissue of rats exposed to microwaves after prolonged exposition period (40 and 60 days).…”
Section: Disscusionsupporting
confidence: 70%
“…The observed increase in MDA level was, according to our results, dependent on the exposure duration. However, we failed to demonstrate the signifi cant change in MDA level in animals exposed to MWs for 20 days, previously reported by (27), probably due to the differences in average SAR (0,09 W/ kg vs 1,2 W/kg) and experimental set up. Melatonin administration to irradiated animals ameliorated the radiation effect on lipid peroxidation in the liver tissuein a signifi cant level.Changes in MDA level in group both irradiated and treated with melatonin occurred simultaneously with the increase in MDA level in irradiated group.…”
Section: Disscusioncontrasting
confidence: 50%
“…Therefore, stimulation of the immune system may be a key mechanism for the induction of adaptive response. On the other hand, some recent studies showed that radiofrequency radiation causes oxidative injury in different tissues mediated by lipid peroxidation, increased level of nitric oxide (NO), and suppression of antioxidant defense mechanism (Esmekaya et al 2011, Ozgur et al 2010. Feinendegen et al (1996Feinendegen et al ( , 1999, in their previous studies, proposed that adaptive response could be induced by reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…EMF inhibited MnSOD expression in the rat testis and induced oxidative stress on heart, lung, testis and liver tissues and testicular apoptosis [32][33][34]. Related animal study has also shown that exposure to ELF induced males mice spermatagonial cells apoptosis [35].…”
Section: Discussionmentioning
confidence: 99%